THE DEVELOPMENT OF MUSCLE MASS AS A MEANS OF INCREASING THE IMMUNE SYSTEM OF A PERSON - Yakubzhonov Ikrom Akramzhonovich; Nurmatov Bahrom Bektemirovich; Gofurov Abduvohid Makhmudovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article examines the peculiarities of the development of modern man, where his daily activity is unthinkable without movement. Movement is the basis of life and longevity. Perhaps only the first is a general concept of relatively insufficient movements and efforts. To what extent it is legitimate to use these definitions to characterize the modern lifestyle of students, we will consider below. After all, it cannot be said that we never get tired, do not feel a decline in vitality, mood, and never feel physically tired. According to many scientists, their lifestyle makes an important contribution to the health of modern youth